Fábulas metarrealistas : realidades grotescas na literatura brasileira contemporânea em “O livro das cousas que acontecem”, de Daniel Pellizzari - Souza, Luciéle Bernardi de (2018)
Through a fabuloustic tour in search of the realities present in Daniel Pellizzari's O livro das cousas que acontecem (2003), I find out the grotesque. Always present, but not always visible, the grotesque is materialized in the fictional reality, but also in the actions and habits of the contemporary subject. We walk together for three chapters, in which there are reflections on Realism, fable and parody, to know how are constructed the grotesque aesthetics of the solid grottos that hide the realities of the work. Stating the recurrent presence of this aesthetics, not only in the literature, but in the cinema and the plastic arts, this reflection becomes essential on days where the "grotesque" is used for arguing for censorship of art. Furthermore, thinking about sensations, actions and feelings that comes to light through such aesthetic manifestation and its multiple unfoldings is also a way of knowing ourselves and the other.